ANALYSIS OF INTEGRATED AND COLLABORATIVE WORKPLACE LEARNING CONCEPTS AS AN IMPLEMENTATION OF WORK-INTEGRATED LEARNING FOR CIVIL SERVANTS (ASN) - Sudewo, Perdhana Ari; Amini, Nabila Syahwa (Politeknik STIA LAN Makassar, 2025)
Law Number 20 of 2023 concerning Civil Servants (ASN) mandates competence development through work-integrated learning. As learner behaviors evolve and the implementation of integrated learning becomes mandatory, the approach to civil servant competence development is transforming. This includes the adoption of experiential learning and learning in the flow of work. Given the large number of civil servants and the limitations of traditional classroom training capacity and budget, a more flexible approach to learning innovation is needed. This study analyzes the implementation of integrative and collaborative workplace learning within government agencies, using the Indonesian Food and Drug Authority (BPOM) as a case study. The methodology used includes literature review and focus group discussions (FGDs). The research findings indicate that integrative and collaborative learning, when designed with the support of workplace facilitators and a system for recognizing learning achievements, can be an effective alternative to traditional classroom training. This approach enables adaptive and continuous learning, aligning with the competency needs of functional positions. This study recommends the government to systematically adopt this learning model, provide supporting infrastructure and an ecosystem, and conduct regular evaluations to ensure program alignment with organizational needs.